2017
DOI: 10.1056/nejmicm1611258
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein Guidance in Glioblastoma Resection

Abstract: A 55-year-old man presented to the emergency department with a 1-week history of severe headache. Magnetic resonance imaging of the brain with and without gadolinium-based contrast agent revealed a rim-enhancing mass (4.5 cm in diameter) in the right temporal lobe. At the time of surgery for tumor resection, fluorescein was administered intravenously (Video); Panel A shows the baseline condition before injection. The intact blood-brain barrier of normal brain parenchyma prevents the uptake of fluorescein; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…6 In addition to evaluating whether the homogenizing process is suitable to obtain at least similar optical properties values by using dissected tissue samples, or whether the interference is too harsh to the tissue's structure, a simplification and thus timesaving aspect of the tissue preparation process accompanied by an increase of reproducibility should be tested. In particular the method of homogenizing is very interesting for small, heterogeneous, or traumatized samples from biopsies or resections (e.g., cholesteatoma 41 and glioblastoma 42 ). As the optical properties of ex vivo samples highly depend on the storage conditions and further processing 7,11,32,43 and may thus decidedly differ from those of in vivo tissue, future work should be focused on the relation between these two kinds of state of tissue conditions.…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition to evaluating whether the homogenizing process is suitable to obtain at least similar optical properties values by using dissected tissue samples, or whether the interference is too harsh to the tissue's structure, a simplification and thus timesaving aspect of the tissue preparation process accompanied by an increase of reproducibility should be tested. In particular the method of homogenizing is very interesting for small, heterogeneous, or traumatized samples from biopsies or resections (e.g., cholesteatoma 41 and glioblastoma 42 ). As the optical properties of ex vivo samples highly depend on the storage conditions and further processing 7,11,32,43 and may thus decidedly differ from those of in vivo tissue, future work should be focused on the relation between these two kinds of state of tissue conditions.…”
Section: Introductionmentioning
confidence: 99%
“…23 Recent observations during our own clinical study of NaFl showed extensive accumulation of the dye outside the vessels shortly after administration, potentially confounding tumor identification. 15 Previous preclinical studies of NaFl in the blood and normal brains of rodents point to a possible explanation for the observed behavior in human brain. Delori et al have reported that NaFl binds to blood proteins only weakly, resulting in the presence of both free and bound forms of the dye in the circulation, 3 while Yen et al and others have reported the presence of NaFl in normal rodent brain tissue, suggesting that the contrast agent crosses the protective barriers in the brain at measureable concentrations.…”
mentioning
confidence: 99%
“…As a matter of fact, some areas, such as dura mater, circumventricular organs and choroid plexus, due to the lack of BBB, appears intensively fluorescent ( 35 ). In addition, although the presence of FS fluorescence in normal brain parenchyma close to tumor tissue has been occasionally shown and considered a consequence of direct surgical manipulation ( 33 , 39 41 ), it has been suggested that the application of a strict intraoperative protocol of FS injection could significantly limit this event ( 35 ).…”
Section: Fluorescein Sodiummentioning
confidence: 99%